Artificial Intelligence and Islamic Law: Testing the Validity of ChatGPT in the Field of Zakat - Fauzul Hanif Noor Athief; Lukmanul Hakim; Tika Widiastuti; Aminullah Furqoni; Marwini (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Technological advancements have shifted the process of knowledge acquisition from textbooks and teachers to individuals independently seeking information through other source. Artificial Intelligence (AI), with ChatGPT as a natural language processing tool, has become one of these references. In Islam, the tradition of learning is emphasized through the transmission of knowledge from teachers, known as sanad, rather than through self-study or autodidacticism. This research focuses on the validity of ChatGPT's responses to user questions on the topic of zakat as one of the pillars of Islam. The study employs content analysis of answers obtained from ChatGPT and compares these responses against three primary references: Yusuf Qardawi's